Production of recombinant p53 protein by PCR-based site directed mutagenesis of plasmid DNA - Bakhtiar, M. Taher; Arief Ichwan, Solachuddin Jauhari; Abdullah, Zafirah L. (2010)
Cancer is defined as a group of neoplastic diseases broadly characterized by abnormalities of cellular differentiation, maturation and control of growth. The mutation of p53 is one of the most common events found in human cancers. The p53 tumor suppressor protein plays a central role in the cellular response to DNA damage by controlling genes involved in cell cycle arrest and apoptosis. When p53 is lost of its function this may permit the cell to divide without control. The purpose of the research is to produce human recombinant protein that mimic a specific mutation of the p53 gene by polymerase chain reaction (PCR) based site-directed mutagenesis of wild type p53 plasmid. In the future, the recombinant protein can be use to prevent or to treat the cancer as a part of gene therapy.